ENT530 : Business Model Canvas: CookiesCo / Ahmad Aiman Ahmad Ikhwan ... [et. al] - Ahmad Ikhwan, Ahmad Aiman; Zulkhairi, Azyla; Che Nordin, Muhammad Aizat Afiq; Ramly, Muhammad Izdihar Fadhli; Shaheezam, Yasmin Azra (2021)
CookiesCo is a start-up business venture that is developed to produce the highest quality cookies and service to our customers. CookiesCo sells cookies with a variety of flavor that is curated to suit our customer’s taste buds and preferences. By using premium ingredients to produce the best quality of delicious cookies, CookiesCo always ensures that our customers are always provided with satisfaction after purchasing our product. Being a start-up business, CookiesCo also encounters a few problems since it has been established, such as the lack of expertise in the field due to being very new to the business. Other than that, in order to gain our customer’s trust and recognition, CookiesCo have to increase efforts in terms of marketing to enhance the brand recognition. Since cookies are a snack that is always in demand, CookiesCo offers a range of flavours for our customers. This way every customer will be left satisfied as our flavor are curated to suit everyone’s preferences due to the variety range of flavours available. On top of that, CookiesCo always ensures that our customers get the best service every single time. CookiesCo is currently in a market that is high in demand, with that we currently have two competitors which are Munchy’s and Famous Amos. One of the strengths that CookiesCo can highlight is the affordable price and range of flavours. The purpose of this Business Model Canvas is to show us on how to create a better flow of doing business and create new ideas to improve the business. Moreover, the content of Business Model Canvas can be used to guide a new start-up business in the industry to identify the important elements that the company